Career development programs and employee retention: Insights from the Ministry of Works in Tanzania - Hindu Augossy; Richard Msacky; Chacha Magasi (International Journal of Academe and Industry Research)
This study examined the relationship between career development initiatives and employee retention at the Ministry of Works in Tanzania. The study was guided by equity theory, which was founded on the assumption that employees tend to remain with their organisation when they are perceived to be treated equally. Cronbach's Alpha coefficient was used to assess the variable’s reliability. A cross-sectional design was employed to collect quantitative and qualitative data from survey questionnaires and interviews. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data were analysed through content analysis. The study found that employee retention at the Ministry of Work is high. In addition, the study findings revealed significant positive effects of career development programs on retention, including education opportunities (coef. = 1.884, p = 0.016), fair career development opportunities (coef. = 1.2122, p = 0.001), and involvement in innovation and creativity (coef. = 1.5216, p = 0.000). Similarly, qualitative findings indicated that career development programs, including educational opportunities, career autonomy, and recognition practices such as awards and promotions, significantly enhance employee retention. The study contributes to existing knowledge by demonstrating that well-structured career development programs significantly enhance employee retention. It is recommended that organizations invest in training, career autonomy, and innovation opportunities to further improve retention rates and reduce turnover.